SMU's gift of a song to commemorate 50 years of National Service - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
The Singapore Management University (SMU) is proud to commission an original song entitled – “I Get You” – as a tribute to commemorate 50 years of National Service (NS50) and to acknowledge the contributions of all in Singapore who have served or continue to serve NS.